Description of Learning Difficulties In Grade X Students of SMK Taruna Karya 1 During a Pandemic - Ramadan, Regi (Asian Journal of Social and Humanities, 2023)
Learning is a process of interaction between educators and students. Covid 19 has currently colonized the country of Indonesia, where the spread of the disease is very fast. The impact of this covid 19 outbreak has not subsided, learning will continue to be carried out from each home (study from home). Online learning should be a learning method that makes it easier for students to continue learning even in a pandemic. But in reality, after being implemented, there are still many shortcomings that cause difficulties for students to feel. Based on the results of observations at SMK Taruna 1 Karawang for 1 week, especially in grade 10, there are students who experience learning difficulties, especially in participating in learning through virtual meeting media and in doing assignments that are assigned tasks are often late and tend to have difficulties due to a lack of understanding in learning caused by the family environment as well as online learning support facilities. The problems that occur in institutions, especially class X, are 2 students who are suspected of having learning difficulties, one is due to supporting factors such as quotas and devices, the second is mainly influenced by the conditions of the house